Issues of Social Conflict in Ke Hujung Usia based on Coser's Functional Conflict Theory: (Isu Pertembungan Sosial dalam Novel Ke Hujung Usia Berdasarkan Teori Konflik Fungsional Coser) (Malay Literature, 2020)
This research intends to prove social conflict in the novel Ke Hujung Usia (2018) by A. Rahman C.M. based on Lewis A. Coser's Functional Conflict Theory, which places conflict as an indicator of a healthy relationship in the social structure. The conflicts presented between characters in the novel include clashes involving Tuk Aki, Tuan Guru Haji Munir, District Office officials, Rasol (the Political Secretary of the Chief Minister), and Umar, who represents the students at Pondok Haji Hamid, and others. The conflicts between the characters have a positive influence on the integration, consensus and strength of the in-group among the students, and on the position of Tuk Aki himself, as the administrator of the centre of religious education. Based on Coser's theory, conflict is not negative because the clashes of out-group are normal due to the positive impact on the strength of social structure. Thus, Coser rejected the argument that absence of conflict is an indicator of the strength and stability of a relationship. Based on the thought of Coser, the conflict between Tuk Aki and the out-group help to strengthen structural relations, in addition to enhancing the integration of the students who are led by Umar. The social group consensus exists because there is two-way communication in the conflict, and because Tuk Aki plays the role of the safety valve to control the conflict.Key Words: functional conflict, in-group, out-group, indicator, safety valve